A rare case of thigh compartment syndrome following ultrasound guided muscle biopsy. (September 2016) - Natalwala, Ibrahim; Taylor, Lauren; Morritt, Andrew
Abstract: Compartment syndrome in the thigh is rare and most frequently follows blunt trauma. Tissue biopsy is frequently performed to obtain a diagnosis for soft tissue lumps. We report a case of thigh compartment syndrome following an ultrasound guided biopsy for sarcoma in order to increase awareness of this rare complication amongst healthcare professionals.